The Influence of Learning Discipline and Environment on Learning Outcomes at the Institut Bisnis Dan Komputer Indonesia - Sitanggang, HD. Melva; Raja, Edward Alezandro Lbn.; Raja, Togu Harlen Lbn. (Journal of Ecohumanism, 2024)
Every pupil and student needs to receive attention in improving their learning outcomes at every level of education they take. In this research, the research variables used are learning discipline (X1) and environment (X2) as independent variables and learning outcomes (Y) as the dependent variable.The research location is the Institut Bisnis Dan Komputer Indonesia where students from the class of 2022 are used as respondents or population and the sample is 45 people.Data was collected using a research instrument in the form of a questionnaire and then processed using SPSS 16. The SPSS processed results show that the influence of discipline on learning outcomes was 95.2%, the influence of the environment on learning outcomes was 92.4%, while the influence of learning discipline and the environment together they influence the learning outcomes of students in the class of 2022 at the Institut Bisnis Dan Komputer Indonesia by 77.4%